Generalization to Type 2 of PSO-Optimized Type 1 PD Fuzzy Controller and its Application to a Quadrotor UAV - Benbrahim, Meriem; Bouhentala, Moufid; Ghanai, Mouna; Chafaa, Kheireddine; Essounbouli, Najib (Engineering, Technology & Applied Science Research, 2025)
This study presents a new Type 2 fuzzy logic (interval-valued fuzzy logic) control system for a Vertical Take Off and Landing (VTOL) quadrotor. The goal of the control design is to obtain robust and stable tracking of the desired angles in the presence of disturbances and noises. The membership functions relative to the linguistic variables of the fuzzy if-then rules are chosen to control the quadrotor to track a reference trajectory. The Particle Swarm Optimization (PSO) method is used to optimize controller-free parameters. The results obtained from an extensive simulation study show that the quadrotor can operate autonomously in flight with stable orientation. The performance of the controller was evaluated for both Type 1 and Type 2 fuzzy controllers. The simulation results show the effectiveness of the proposed controller and its better performance.